For teachers of babies: a profession marked by subtlety - Fernanda Carolina Dias Tristão (Universidade Federal de Santa Catarina, 2004)
This article aims to present some thoughts about the education of babies in collective spaces, building upon a search conducted in a nursery for the municipality of Florianópolis / SC. From the analysis of material collected in this nursery I could find that the pedagogical work carried out with little boys and girls is marked by subtlety of the shares present in relationships between teachers and children, who often are not perceived in the daily routine, but which are crucial in characterization of this profession. This subtlety is permeated by a complex involving the perception of each of the children, against the background of the role of education for teachers and the humanization of these small humans.